2015
DOI: 10.1016/j.freeradbiomed.2015.01.035
|View full text |Cite
|
Sign up to set email alerts
|

MKK3 mediates inflammatory response through modulation of mitochondrial function

Abstract: Mitochondria are increasingly recognized as drivers of inflammatory responses. MAP kinase kinase 3 (MKK3), a dual-specificity protein kinase, is activated in inflammation and in turn activates p38 MAP kinase signaling. Here we show that MKK3 influences mitochondrial function and acts as a critical mediator of inflammation. MKK3 deficient (MKK3−/−) mice and bone marrow derived macrophages (BMDMs) secreted less cytokines than wild type (WT) after LPS exposure. There was improved mitochondrial function, as measur… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
13
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
6

Relationship

3
3

Authors

Journals

citations
Cited by 18 publications
(13 citation statements)
references
References 39 publications
0
13
0
Order By: Relevance
“…Mice that are negative for MKK3 (the upstream effector of p38) exhibited reduced NF-κB and inflammasome activity in response to LPS. In the normal setting, mitochondrial ΔΨm is reduced, mtROS is elevated, and ATP levels fall upon LPS treatment (Srivastava et al, 2015). MKK3 knockout animals are protected from loss of ΔΨm suggesting the activation of p38 MAP kinase pathway elicits inflammatory signals by potentiating mitochondrial dysfunction to engage inflammatory signaling.…”
Section: Mitochondrial Dysfunction and Damp Signaling In Inflammationmentioning
confidence: 99%
“…Mice that are negative for MKK3 (the upstream effector of p38) exhibited reduced NF-κB and inflammasome activity in response to LPS. In the normal setting, mitochondrial ΔΨm is reduced, mtROS is elevated, and ATP levels fall upon LPS treatment (Srivastava et al, 2015). MKK3 knockout animals are protected from loss of ΔΨm suggesting the activation of p38 MAP kinase pathway elicits inflammatory signals by potentiating mitochondrial dysfunction to engage inflammatory signaling.…”
Section: Mitochondrial Dysfunction and Damp Signaling In Inflammationmentioning
confidence: 99%
“…In line with this concept, a recent study has shown that pyruvate kinase M2- HIF-1α mediated Warburg effect drives mortality in sepsis (Yang et al, 2014 ). Our data on macrophages indicates that preservation of mitochondrial function under inflammatory conditions leads to attenuated cytokine responses (Srivastava et al, 2015 ). The mechanism by which metabolic switching regulates inflammatory processes is a novel and promising area of research.…”
mentioning
confidence: 69%
“…Proteomic characterization of the effect of MKK3 deletion in bone marrow derived macrophages (BMDM), which provides data on MAP kinase signaling targets [2], [3], [4], [5], [6], [7].The BMDM proteomics data (total and phospho) has been presented which can be used as a reference for other inflammatory signaling molecules in MAP kinase pathway.The major canonical pathways affected after cigarette smoke in WT and MKK3 deleted BMDM are presented and can be utilized to interrogate the role of MAP kinases in other signaling schemes in cigarette smoke induced injury.…”
Section: Value Of the Datamentioning
confidence: 99%
“…Proteomic characterization of the effect of MKK3 deletion in bone marrow derived macrophages (BMDM), which provides data on MAP kinase signaling targets [2], [3], [4], [5], [6], [7].…”
Section: Value Of the Datamentioning
confidence: 99%